Numerical study of ethylene bubble rising in benzene flow; Petroleum and Coal; Vol. 60, iss. 1 - Khlebnikova E. S. Elena Sergeevna; Vorobjev A. M. Anatoly Mikhaylovich; Ivashkina E. N. Elena Nikolaevna; Lyubimova T. M. Tatjyana Petrovna (2018, 2018)
Title screen